2014
DOI: 10.1007/s11250-014-0541-5
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, prevalence, and risk factors for infection by shiga toxin-producing Escherichia coli (STEC) in dairy cattle

Abstract: Rectal swabs of 198 Holstein × Gir crossbred beef cattle from 34 milk farms in the central west of Brazil were analyzed from August 2010 to February 2011. Strains of shiga toxin-producing Escherichia coli (STEC) were isolated from 72.73% (144/198) of the animals, on over 97% of the surveyed properties. The molecular characterization indicated the most common toxin gene stx1 in 70.88% of the animals (202/285), followed by 18.95% (54/285) stx1/sxt2, and 10.18% (29/285) stx2. The presence of STEC in animals toget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 20 publications
0
17
1
1
Order By: Relevance
“…Although studies to date have not assessed aEPEC prevalence, other studies of stx and O157:H7 dairy prevalence have shown both higher (72·7%, 11·1-32·3%) [15,18] and lower (1%) levels [10]. Importantly, high-shedding cattle have been hypothesized to influence herd EHEC propagation, and only one was observed in the current study [21,22].…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Although studies to date have not assessed aEPEC prevalence, other studies of stx and O157:H7 dairy prevalence have shown both higher (72·7%, 11·1-32·3%) [15,18] and lower (1%) levels [10]. Importantly, high-shedding cattle have been hypothesized to influence herd EHEC propagation, and only one was observed in the current study [21,22].…”
Section: Discussioncontrasting
confidence: 55%
“…Even though O157 is ubiquitous in dairy herds across the United States, risk factors for colonization and shedding dynamics have more commonly been studied in beef herds [12,13]. Dairy studies are especially relevant due to the increasing popularity of drinking raw milk, and the fact that high prevalence levels of O157 have been noted in the few published studies [14][15][16][17]. Previous work has shown several environmental risk factors for dairy O157 shedding, including season, temperature, humidity, rainfall and solar exposure [17].…”
Section: Introductionmentioning
confidence: 99%
“…Studies by Ferreira et al (2014) and Freitas-Filho et al (2014) were pioneering in determining the prevalence of STEC and STEC/O157:H7 in healthy cattle in the State of Goiás, Brazil, while our study evaluated the virulence factors and antimicrobial resistance in STEC isolates obtained from healthy sheep in this State. On the contrary, Blanco et al (2003) found a higher prevalence of non-O157 STEC in sheep compared to cattle, where our study did not reveal the difference between sheep (78.3%) and cattle (72.7%) .…”
Section: Discussionmentioning
confidence: 99%
“…STEC O157:H7 is commonly found in the intestines of cattle and it can contaminate carcasses at slaughter (Hussein and Bollinger 2005). Humans can be infected by consumption of food and water contaminated with animal faeces (Ferreira et al 2014). STEC O157:H7 causes diarrhoea, haemorrhagic colitis, haemolytic-uremic syndrome (HUS) and thrombotic thrombocytopenic purpura in humans (D'Astek et al 2012;Chui et al 2015).…”
mentioning
confidence: 99%